Flying triangulation - A motion-robust optical 3D sensor for the real-time shape acquisition of complex objects - Häusler, Gerd; Ettl, Svenja; Arold, Oliver; Yang, Zheng (Applied Optics, 2012)
Three-dimensional (3D) shape acquisition is difficult if an all-around measurement of an object is desired or if a relative motion between object and sensor is unavoidable. An optical sensor principle is presented-we call it "flying triangulation"-that enables a motion-robust acquisition of 3D surface topography. It combines a simple handheld sensor with sophisticated registration algorithms. An easy acquisition of complex objects is possible-just by freely hand-guiding the sensor around the object. Real-time feedback of the sequential measurement results enables a comfortable handling for the user. No tracking is necessary. In contrast to most other eligible sensors, the presented sensor generates 3D data from each single camera image.
Keywords: optical 3D metrology; motion robust; triangulation